Preventing Psychological Wear in Healthy Organizations. Research in the State of Hidalgo, Mexico - Garcia, M. Angeles Carrion; Gracia, Tirso Javier Hernandez; Baron, Francisco Lopez; Garcia, Alejandra Corichi (European Scientific Journal, ESJ, 2016)
Materials and methods: Non-experimental, cross-sectional quantitative study of 188 employees in different business sectors, State of Hidalgo, Mexico. Instrument: a battery for the study of psychosocial work conditions “CTCPS-MAC”. A bivariate and multivariable logistic regression analysis was made with IBM SPSS Statistics 21 of psychological wear and psychosocial factors. Results: Work Context (p=0.000 Exp (B) = 5.565) infers a greater risk of cognitive-emotional psychological wear. Behavioral level: individual factors (p=0.000 Exp (B) = 8.531) and work context (p=0.000 Exp (B) = 4.759). Physiological level: work content (p=0.000 Exp (B) = 8.765) Conclusions: Probability of psychological wear at the behavioral level: 94.87% in employees with a negative perception of their personal traits and the work/family interrelation. Physiological level: 97.70% for employees in the morning or morning/afternoon shift, good perception of individual factors regarding their personal traits and psychological risk buffers and a bad perception of company characteristics, equipment and physical agents.